FACTORS CAUSING THE LOW LITERACY CAPABILITY OF CLASS 5A STUDENTS IN PRIMARY SCHOOL NEGERI 22 BANDA ACEH - Katrunnada; Siti Mayang Sari; Fitriani Manurung (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Literacy is very important for students in elementary schools in learning,because literacy skills influence students' learning success at school and willalso influence skills in students' daily lives. Low literacy skills can make itdifficult for students in the learning process. Researchers want to know whatfactors cause low literacy in class V at SDN 22 Banda Aceh. This research usesa qualitative descriptive method through the results of questionnaires,interviews and observations, carried out in the VA class of SDN 22 BandaAceh. Meanwhile, the research subjects were fifth grade elementary schoolstudents and parents of students in that class who were classified into threecategories, namely students who had high, medium and low Initial LiteracyAbility (KLA). The research results found that the factors causing students' lowliteracy skills were: (1) the socio-economic situation of the family; (2)communication and guidance for children at an early age; (3) communicationand tutoring during school; (4) reading book facilities/collections at home; (5)cellphone, computer, television facilities; (6) gender; (7) relationships betweenfamily, school and community; and (8) use of strategies/models in learning toread. Based on these findings, it can be recommended: (1) fulfillment of literacysupport infrastructure, (2) intensive guidance, especially in reading activities athome, (3) use of reading learning models in the learning process in elementaryschools.